Penerapan Algoritma Klasifikasi Dalam Menganalisis Loyalitas Pelanggan Sriwijaya Air Di Bandara Kualanamu International Medan - Ginting, Erika; Gemasih, Husna (Jurnal Bisnis Digital, 2025)
In Data Mining there are several algorithms commonly used to perform the classification process. One of them is the Naive Bayes algorithm. Testing results done by using Software Rapid to determine customer loyalty to Sriwijaya Air flight. Variables that were processed in this research were eight variables prepared using questionnaires. Implementation is done in Sriwijaya Air 's departure lounge at Kualanamu International Airport. Then the data is formed using the decision tree process to see the results of data accuracy. The test results are able to provide a useful service strategy analysis for Sriwijaya Air airline although the accuracy level is  86,67% but it will greatly help airlines improve what services become weakness up to now.